DEVELOPING VERBAL-LINGUISTIC INTELLIGENCE IN FUTURE TEACHERS: METHODOLOGICAL FOUNDATIONS AND APPLIED TECHNIQUES - Rano Rashidova (Journals Park Publishing, 2025)
This article analyzes the theoretical foundations of developing students' verbal-linguistic intelligence, as well as the methods, exercises, and practical tasks that contribute to its formation. Verbal-linguistic intelligence is explained through psychological and pedagogical approaches and is examined in connection with communicative skills, oral and written speech, and the culture of communication.
Keywords: Verbal-linguistic intelligence, written speech, oral speech, essay, exercises, communicative competence, teaching methods.